Anthropometric and motor performance variables are decisive factors for the selection of junior national female volleyball players - Tsoukos, A.; Drikos, S.; Brown, L. E.; Sotiropoulos, K.; Veligekas, P.; Bogdanis, G. C. (Journal of Human Kinetics, 2019)
This study examined whether anthropometric and fitness tests might successfully predict selection of young female volleyball players for a junior national team. Sixty four female players (age: 14.4 ± 0.5 y, body height: 1.76 ± 0.05 m, body mass: 63.9 ± 6.4 kg) underwent a selection procedure for the junior national team. Anthropometric data and speed and power test results were obtained and players were graded for their performance in a volleyball tournament. Selected players differed from the non-qualified in body height (3.4%; p = 0.001), standing reach height (2.6%; p = 0.001), the sum of skinfolds (15.4%; p = 0.035), body mass index (BMI; 7.1%; p = 0.005) and spike jump and reach (SJR) (2.5%; p = 0.001). Selected players were classified in the 99.2 ± 1.6 percentile in body height and in the 51.4 ± 20.6 percentile in the BMI, which were significantly different from those of the non-qualified players (95.4 ± 7.0 and 66.7 ± 18.6, p = 0.02 and p = 0.004, respectively). Stepwise discriminant analysis yielded a discriminant function (p < 0.001, Etai2 = 0.78) that was highly loaded by height, SJR and the BMI (r = 0.79, r = 0.74 and r = -0.53, respectively). Cross validation results showed that selection was correctly predicted in 15 out of the 20 selected players (predictive accuracy: 75.0%) and in 35 out of the 44 non-qualified players (predictive accuracy: 79.5%). In conclusion, body height, the BMI and SJR height successfully discriminated between selected and non-qualified elite young female junior national team volleyball players. The equal vertical jump, sprint and agility of selected and non-qualified players, highlight the importance of body height and the BMI for selection of elite junior female volleyball players.